Methods and strategies of provocative role behaviour of text-based internet communication participants - Lazouski, Aliaksander V. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
This article examines the definitions «provocative behaviour», «provocative role behaviour» and «internet trolling». The influence of the ability of internet communication participants for selective self-presentation on the specifics of the formation of their online identity is characterized. The data on the study aimed at identifying methods and strategies of provocative role behaviour of the users of Belarusian news web resource TUT.by and Russian social network VKontakte is presented. 36 methods of category «active aggression», 16 methods of category «passive aggression» and 18 methods of category «supportive behaviour» are described, four strategies of provocative role behaviour are specified.